50.9k views
1 vote
Part 1.] Which of the following is the inverse of the given function?


y= 3 x^(5)-4
A.]
y= \sqrt[5]{ (x+3)/(4)}
B.]
y= \sqrt[5]{ (x-4)/(3)}
C.]
y= \sqrt[3]{ (x+4)/(5)}
D.]
y= \sqrt[5]{ (x+4)/(3)}

Part 2.]  What is the inverse of the function 


y=3 e^(-4+1)?
A.]
y= (1-log(x-3))/(4)
B.] 
y= (1-log( (x)/(3)))/(4)
C.] 
y= (1-ln(x-3))/(4)
D.] 
y= (1-ln( (x)/(3)))/(4)

1 Answer

3 votes
1. I believe the answer is D, y = fifth root of (x+4)/3
y = 3x⁵ - 4
Interchanging x and y
x = 3y⁵ - 4
solving for y in the equation; x=3y⁵-4
y = ((x+4)/3)^1/5

= ((x+4)/3)^1/5

2. inverse of the equation y = 3e^-4x+1
I think the answer is D;
Interchanging the variables x and y
x= 3e^-4y-1
Solving for y in x = 3e^-4y +1
y= -(In(x/3)-1)/4
= (1-In(x/3))/4


User Jgthms
by
6.2k points